Diplomasi Ekonomi Indonesia dan Negara-negara Berkembang dalam G-33 untuk Mempromosikan Proposal Special Products dan Special Safeguard Mechanism - Mariane Delanova (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2016)
Agriculture is an important sector for developing countries because so many people make their living from this sector. Agriculture in developing countries also related to the issues such as food security, poverty alleviation, and rural development. In the era of globalization, interstate trading ruled World Trade Organization (WTO). Agriculture has became one of negotiation sector and has ruled in Agreement on Agriculture (AoA). Developing countries in Group 33 (G-33) in WTO fight for their national interest in agriculture by promoting the proposal of Special Products (SP). This proposal of SP defines the agriculture’s products that are sensitive and related to food security, poverty alleviation, and rural development. This research aims at analizying the strategies of economic diplomacy of developing countries, especially Indonesia in the multilateral trade of WTO.